Implementasi Manajemen Program Tahsin Metode Tilawati dalam Peningkatan Kualitas Pembelajaran Al-Qur’an di MI Bani Ridwan - Khamima, Bilqis Auliatul; Thohir, Muhammad (JoIEM (Journal of Islamic Education Management), 2024)
This research carefully reviews the implementation of the tilawati method management in Al-Qur'an learning at MI Bani Ridwan. The focus is to investigate how to implement the tilawati method with students. The research subjects involved include ustadz, ustadzah, santri, and the object is the implementation of the tilawati method in learning to read the Koran at MI Bani Ridwan. In collecting data, researchers used various techniques such as observation, interviews. The collected data is then described in the discussion. The research results show that good management of the Tilawati Method Tahsin program contributes significantly to the success of the program. Management strategies involving regular training for teachers, regular evaluations, and the use of technology in teaching have proven effective. This success is reflected in the deep and precise understanding of the ustadz and ustadzah in implementing appropriate management in the tilawati method tahsin program. By using the tilawati method, Al-Qur'an learning at MI Bani Ridwan is able to create an environment that combines both spiritual understanding and academic strengthening with full brilliance.